Communicate Contemporary Art without Visiting the Museum without Visiting the Museum: The Reina Sofía Museum during the confinement by Covid-19 - Gonzálvez Vallés, Juan Enrique; Caerols Mateo, Raquel; Cabezuelo Lorenzo, Francisco; Viñarás Abad, Mónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
The Reina Sofia Museum is the most visited Spanish museum. Its activity in social networks during the confinement due to the health pandemic in the spring of 2020 was very relevant. The aim of this work is to analyze the relationship between the Museum and the public, the discourse in social networks and participation. The methodology consists of an in-depth interview was conducted with the person in charge of communication and an analysis of the content of their social network. The results show a high level of public participation and a proactive strategy based on content, hashtags and active listening.